Application of computational techniques in the development of programs and their mathematical modeling (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
No technical achievement has so affected the intellectual human activity, like electronic computers. Increasing in tens and hundreds of millions of times the speed of execution of arithmetic and logical operations, thereby enormously increasing the productivity of intellectual human labor, computers caused fundamental changes in the field of education information boots. At the beginning of the 21st century, computers have become so advanced that there is a real opportunity to use them in scientific research cations, not only as large adding machines, but also to apply with their help you to the study of such branches of mathematics, which were previously practically not available for research. This was realized even when deciding on noncompliance. advanced computers complex mathematical problems of nuclear physics, ballistics, applied celestial mechanics